Short Communication: A new variety of Pholiota microspora (Agaricales) from Nepal - MAHESH K. ADHIKARI; KAZUO WATANABE; G. P. PARAJULI (Society for Indonesian Biodiversity, 2014)
Adhikari MK, Watanabe K, Parajuli GP. 2014. A new variety of Pholiota microspora (Agaricales) from Nepal. Biodiversitas 15: 101-103. In the fall of late rainy season 2011, a new Pholiota (Fr.) P. Kumm. (Agaricales, Strophariaceae) was collected in the Quercus forest of Phulchowki (Kathmandu valley) along the trial line, on the dead log at an altitude of 2600m. The specimen gathered was quite small. It was brought to laboratory and cultivated in NARC, Pathology laboratory, Lalitpur, Kathmandu, Nepal. The mushroom has been identified as Pholiota microspora (Berk.) Sacc. var. himalensis var. nov..